Use of land resource assessment to estimate potential fodder outputs and animal support capacities in some countries in West Africa - Mohamed-Saleem, M.A.; Velthuizen, H.T. van; Kaufmann, Ralph R. von (French Grassland Society, 1989)
Presents the result of a study conducted to estimate the potential fodder productivity of millet, sorghum, maize and rice using the land suitability estimates of FAO and the AEZ metheodology for Stylosanthes hamata cv verano. Also examines the dry matter theat could be produced from 0.5 percent of the suitable land at low and high inputs.